Potential and cumulative accessibility of workplaces by public transport in Szczecin - Goliszek Sławomir; Połom Marcin; Duma Patryk (Bulletin of Geography. Socio-Economic Series, 2020)
The article presents the accessibility of workplaces in Szczecin using the method of potential and cumulative accessibility for commuting by public transport. The public transport commuting times used in the study were generated using the public transport model, which was developed based on data in the General Transit Feed Specification (GTFS) format. The results of potential accessibility by public transport were calculated for several selected time thresholds in the morning rush hours between 7 a.m. and 9 a.m.. On the other hand, cumulative accessibility is characterised by variability of travel times for 8 a.m., which is calculated in 10- to 60-minute intervals of travel time. The aim of this study is to identify workplaces in Szczecin that are situated in areas where accessibility is more dependent on the parameters of the public-transport timetable. In addition, a possibility to define the optimal journey length was assumed so that it would regard the largest number of jobs. The use of the two indicated research methods for the accessibility of workplaces in Szczecin provides a result in the form of better- and less-accessible areas of the city as regards the labour market. The results regarding the accessibility of workplaces using the two methods identify places of increased demand for commuting by public transport during the morning rush hours.